Food Knowledge and Practices Related to Anemic Conditions among Pregnant Women in Kuala Terengganu, Malaysia - Bah, Faatimah; Harith, Sakinah; Farisni, Teungku Nih (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2020)
Anaemia is defined as a condition indicated by the deficiency of red blood cells (RBCs) or haemoglobin (Hb), and anaemia is still said to be the most prevalent nutritional deficiency during pregnancy. It is a huge contributor to maternal mortality. During pregnancy anaemia not only affects the mother but also the growing foetus, which makes it more dangerous. It has been estimated that nearly half of pregnant women around the world are estimated to be anaemic. Previous studies done in Malaysia found the overall prevalence of anaemia among pregnant women to be 35%. Knowledge in regard to anaemia and food practice are factors that contribute to anaemia. This study aims to determine the relationship between food practices, knowledge in regard to anaemic conditions among pregnant women in Kuala Terengganu. The study was based on samples gathered from 96 pregnant women from Hiliran Health Clinic in Kuala Terengganu. Data collected was based on self-administered questionnaire and twenty-four-hour diet recall. The data was analysed using Statistical Package for the Social Sciences (SPSS) version 21.0. The prevalence of anaemia was found to be 40.9% and no association was found between anaemia and sociodemographic factors among pregnant women in Kuala Terengganu. Anaemic pregnant women achieved a higher average score of knowledge regarding anaemia as compared to non-anaemic pregnant women. In conclusion findings of this study suggests that there is average knowledge of anaemia among the given population. Findings also suggest that the overall population had good food practice. Furthermore, implications of the study findings, limitations, and directions for future research were also discussed.